Zapotrzebowanie rolnictwa na siłę roboczą w planowaniu regionalnym - Maj, Bolesław (Wydział Prawa i Administracji UAM, 1970)
Methods of estimating the demand for labour force in agriculture have three common features: they are based on the empirical analysis of effectiyity of labour, they aim the estimating of the interdependences "labour — production" in optimum, and their norms depend on the conditions of place and time. According to these features the methods can be systematized. Among the methods that adapt the occupation norms directly from agricultural practice, or that use as the norm the indicators of changes in volume of labour, or base on the function of production, the third group of methods proved to be the most useful in regional planning. The third group is represented by simplified Klatzman's method published in: Cahiers de l'Institute de Science Économique Appliquée in Paris. Adaption of the method in regional planning of this country would proof advantageous under the condition of taking into account the differences of French and Polish planning.
Demand of Agriculture for Labour Force in the Regional Planning